Nested association mapping population in japonica rice: Development, characterization, and application in genome-wide association studies - Bhagwat Nawade; Sang-Ho Chu; Sunhee Kim; Chang-Yong Lee; Jinsong Bao; Yong-Jin Park (Current Plant Biology)
Multiparental mapping populations hold great potential for dissecting quantitative traits and rapidly identifying genetic determinants. We developed a japonica nested association mapping population, KNU_NAM, comprising 880 lines derived from ten recombinant inbred lines (RILs) families of prominent varieties and the elite Korean variety Shindongjin. Genetic characterization of KNU_NAM revealed 48,159 polymorphic SNPs, with family counts ranging from 18,787 to 42,578 and an average of 30,019 SNPs per family. Further molecular diversity analysis of KNU_NAM indicated reduced population structure and broad genetic diversity. Genome-wide association studies (GWAS) on five morphological traits identified 47 significant marker-trait associations (MTAs), with a set of 18 MTAs located on chromosome 9. Linkage disequilibrium (LD) block analysis of this region revealed 15 haplotypes and identified five key genes associated with panicle architecture: OsDEP1, OsEATB, OsLGD1, and OsSPL18. Additionally, two non-synonymous MTAs on chromosome 7 were located on the exon of OsPRR37/Ghd7.1, a gene associated with plant height, heading date, and grain number per panicle. Further phenotypic performance analysis of haplotypes from these hotspot regions revealed significant differences in the targeted traits. The study validates the potential of KNU_NAM and GWAS for high-resolution genetic mapping in rice breeding programs, highlighting the utility of these populations for enhancing genetic diversity and improving trait selection in rice.